Medan International Convention Center in North Sumatera Province (Expressionism Architecture) - Samsul Bahri; Afrida Handayani (Talenta Publisher, 2017)
Medan is the capital province of North Sumatera in Indonesia. Medan has developed to become one of the metropolitan cities in Indonesia and the heart of economic growth in North Sumatera. Nowadays, Medan is the core of commercial and economic in Indonesia. As the business city, Medan needs a facility as a medium for many activities such as meeting, incentive, conference, an exhibition in world scale. Constructing Medan International Convention Center will be helpful for Medan society and surroundings in needing the daily needs by construction the multi-purpose building. Convention center is one of the valid proof in the convention industry, giving the economic contribution to the city. Considering the substantive investment in the convention center in last years enhances the competition among the businessmen. During the process of designing the Medan International Convention Center uses the method by doing library study which aims to gain the explanation about the program, the field study in gaining the physical data which is needed and literature study as the reference or comparison in designing. Medan International Convention Center can be visited 4000 until 7000 people. The theme of expressionism architecture applies to the building which will show the shape that it can communicate and create the feeling and emotion of the function itself. Finally, this building has the proper function, having the good and visual interest.